Bahasa Inggris - Nurrika Febriyanti Kusnadi; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2023)
Utilizing the RADEC learning paradigm (Read, Answer, Discuss, Explain, Create) to help students comprehend the concept of energy transformation through Rasch model analysis is the goal of this study. From the get-go in 2023, 32 students filled in as the example for this quantitative spellbinding exploration project. The Pre-Test and Post-Test data were examined with the help of the Rasch Stacking Analysis model. The results showed that when the RADEC learning approach (Read, Reply, Talk about, Make sense of, Make) was utilized, the two understudies with low and high capacity levels worked on in their ability to figure out subjects. RADEC represents Read, Reply, Examine, Make sense of, and Make. trains understudies for autonomous and bunch learning. Students are expected to solve problems on their own after reading and responding. Then, at that point, understudies work as dynamo fans following the idea of energy change material. The group then presents an explanation of their work or discussion to the other groups. In the wake of following the punctuations as seen from the aftereffects of the pretest and posttest, which are handled utilizing the Rasch stacking examination modelin the RADEC learning model, understudies can deliver logit values that are generally excellent at 37.5% and great at 62.5%.